MPLEMENTASI PRINSIP-PRINSIP PENGEMBANGAN KURIKULUM PADA PENDIDIKAN ISMUBA DI SD MUHAMMADIYAH - iswanto iswanto; Hendro Widodo (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
Alternating the curriculum in almost every period of the Ministry of Education makes the education unit must follow and implement what is the policy of the Ministry of Education. The curriculum is one of the important components in achieving educational goals in schools. Not except in Muhammadiyah schools, which have curricula from elementary schools and primary and secondary education assemblies of Muhammadiyah's central leaders. So, so that curriculum development in schools does not come out of the development rules, every educational institution must refer to the principles in curriculum development. The purpose of this study is to find out the implementation of the development of curriculum principles in ISMUBA education at SD Muhammadiyah Kadisoka, Purwomartani, Kalasan, Sleman. The method used in this study is field research. From the results of the study, it is known that the Muhammadiyah Kadisoka Elementary School has successfully implemented the principles of curriculum development in ISMUBA learning and has met the achievement indicators.